An Ethical Analysis of the Application of the Death Penalty in Islamic Law - Karimullah, Suud Sarim; Nanda Ahmad Basuki; Arif Sugitanata (ANTMIND YOUTH EMPOWER FOUNDATION, 2024)
The application of the death penalty is a subject that triggers complex ethical and moral debates, demanding deep and critical thinking regarding the fairness, effectiveness, and humanity of the legal system in place. This study aims to provide an in-depth understanding of the interpretation and application of the death penalty in the context of Islamic law and consider its compatibility with contemporary ethical norms and human rights principles. Through the library research method, this study integrates and comprehensively analyzes relevant literature to explore various perspectives and sources that have been carefully examined. The findings of this study indicate that the death penalty in the context of Islamic law is not just a simple juridical issue but also requires deep and layered ethical considerations. These considerations must include a thorough understanding of the social and cultural context and readiness to respond to the inevitable dynamics of changing times. It is also important to always respect and uphold the fundamental values of Islam, which include respect for life, fair justice, and broad generosity in maintaining order and security.